Kerk en staat in de Orthodoxe wereld: Wat is de plaats van godsdienst in de publieke ruimte? - Kalaïtzidēs, Pantelēs (Tijdschrift voor theologie, 2017)
The present paper offers first some introductory remarks of historical and sociological order, and a brief critical theological reflection on the Byzantine ideal of ‘symphonia’ as a common politico-cultural background behind the different types of relationship between Church and State in the Orthodox world. Secondly, it confronts the dominant model of Church-State relations in the so-called Orthodox countries with the fundamental principles of secularization, and poses the crucial question of the compatibility between Orthodoxy and modernity, as well as the more general question of the place of religion in public space. The conclusion of the paper mainly deals with the public witness of the Church and theology in the framework of post-modern pluralistic societies. The guiding idea of the paper is that an Orthodox answer to modern challenges cannot be found on the side of the Byzantine ‘symphonia’, nor on that of the ‘nationalized Orthodoxy’ and the Orthodox statism. Inspired by the eschatological self-consciousness of the Church, and the dialectic between the ‘already’ and the ‘not yet’, the paper calls for a fruitful engagement of the Orthodox Church in a struggle for internal spiritual renewal and reformation, as well as the adoption of an ecumenical ecclesiastical discourse, free from the continuous references to the nation and to the outward forms of the Constantinian era, as an absolutely urgent prerequisite, and inviolate condition for Orthodoxy, to participate in the century in which we live away from any escapist move towards the past.